q-Double Cesaro Matrices and q-Statistical Convergence of Double Sequences - Cinar, Muhammed; Et, Mikail (Springer India, 2020)
In this study, we introduce and examine the concepts of q-double Cesaro matrices and q-statistical convergence and q-statistical limit point of double sequences. Also, we give some relations connected to these concepts.
Keywords: q-Integers; Statistical convergence; Cesaro summability